Profiling of bacterial transcriptome from ultra‐low input with MiniBac ‐seq - Tianmin Wang; Ping Shen; Ruochen Chai; Yihui He; Jintao Liu (Environmental Microbiology, 2022)
There is a lack of appropriate methods for preparing bacterial RNA‐seq library with ultra‐low amount of RNA. To address this issue, we developed miniBac‐seq, a strand‐specific method for high‐quality library construction from sub‐nanogram of total RNA, which is 100‐fold lower than the current benchmark kit and dramatically reduces preparation cost ($28 + $15 × samples). We further demonstrated the high sensitivity of miniBac‐seq via detecting more than 500 genes from amount of total RNA equivalent to that of a single bacterial cell. Finally, we profiled the transcriptome of growth‐arrested bacteria in isogenic culture of Escherichia coli . This subpopulation of bacteria is generally low in abundance but is a potent reservoir of antibiotic persistence, and their gene expression has been largely unknown due to technical limitations. Using miniBac‐seq, we identified potential molecular driver towards arrested growth as well as antibiotic tolerance. Our method thus expands the capacity to quantify bacterial transcriptome in situ, which is useful to the understanding of bacterial physiology and regulation in their native contexts.